PENGARUH JARAK AIR GAP PADA PERFOMANCE MOTOR BRUSHLESS DIRECT CURRENT JENIS EXTERIOR ROTOR - Huda, Thorikul; Indriani, Nita; Efrizal Gozali, M (LPPM ITK, 2017)
Electric motors today have become an important part in technological developments. One type of electric motor that has been and continues to be developed at this time is brushless direct current (BLDC). BLDC is generally applied as an actuator on electric vehicles. The development of electric vehicles make BLDC motor more varied. This research analize the influence of air gap distance on the design performance of BLDC motor with exterior rotor type. The BLDC motor has rated voltage 48 V and input current 23A.